Checklist of Civilizations and Culture. - Kroeber, A.
1 online resource
Keywords: "Checklist of Civilizations and Culture contains all known principal civilizations and cultures of the world, with such definition as is possible of their area and time, their subdivisions and periods, and a brief indication of their character. The terms civilization and culture are used inclusively as essential synonyms of varying emphasis. There is no special difference between how the two words are used. They denote somewhat distinguishable grades of degree of the same large scale processes. Civilization currently carries an overtone of high development of a society; culture has become a customary term of universal denotation, applicable alike to high or low products and heritages of societies. This component or segment of culture or civilization is denoted here as ""value culture"" by A.L. Kroeber. It includes all purely aesthetic and intellectual activity as well as an element in every religion, and includes some part of morals, though morality is directed also to personal conduct and action. Every human society has its culture, complex or simple. The word culture should denote all possible ideals, but for the larger and richer cultures the term civilization may be more appropriate. Kroeber argues that the problem of recognizing the world's cultures is essentially one of natural history and involves dealing with all phenomena and then building up their patterns or classes step by step. This classic volume is now available in paperback. No better teacher of general anthropology can be imagined than A.L. Kroeber."--Provided by publisher.